Holistic Localized Performance Assessment (HOLPA) tool for collecting evidence on the impact of agroecology - Jones, Sarah; Sanchez, Andrea (2024)
HOLPA is a survey-based tool for collecting evidence of the holistic impact of agroecology. It contains three modules: context, agroecology adherence, performance (global, local). It is applicable at plot, farm-household, or landscape levels (only piloted at farm-household level so far). Questions are coded for use in KoboCollect, an app for Android tablets. The presentation provides an overview of the tool and initial results from performance assessments carried out under the CGIAR Initiative on Agroecology.